STUDI SINTESIS DAN PEMBANGKITAN RESONANSI PLASMON TERLOKALISASI DARI NANOPARTIKEL PERAK UNTUK APLIKASI SENSOR KOLORIMETRI - Labiba, Alifah
Metal nanoparticles such as gold and silver are often used in various nanotechnology applications due to the localized plasmon resonance effect that occurs when incident photons interact with metal nanoparticles. In general, metal nanoparticles require molecular capping to prevent nanoparticles from aggregating or interacting with other molecules. 3-mercaptopropionic acid (3-MPA) is one of the molecules that can be provided for surface functionalization because it has a thiol group and a carboxylic group that can be used as a linking biomolecule and this allows the use of nanoparticles for biosensor applications. The use of gold or silver nanoparticles for biosensor applications has been widely studied, but so far the sensitivity and accuracy of biosensor devices in detecting the type of analyte to obtain good results still continue to be achieved. Whether it is done by variations in shape, size of nanoparticles, and also the capping material. The aim of this study is to study the synthesis of silver nanoparticles using trisodium citrate and 3-MPA molecular capping using a modified reduction method in which citrate and 3-MPA are added to AgNO3 as precursors. The characterization results show that Ag-Citrate with AgNO3 concentration of 1.5 mM had a sharp plasmonic peak at 428 nm in the absorbance spectrum and spherical shape with a diameter of less than 100 nm. Ag-MPA with AgNO3 concentration of 1.5 mM shows an absorbance curve with plasmonic peaks that seem to shift towards short wavelengths (422 nm) due to capping modification using 3-MPA for citrate capping. Fourier Transform Infra Red (FTIR) characterization show that the coordination of the citrate molecule and Ag-citrate are quite different. Asymmetric COO- in free citrate is at a frequency of 1591 cm1 , whereas when citrate is on Ag it shift to 1599 cm-1. The symmetric COO- band also shifted from 1395 cm-1 for free citrate to 1385 cm-1 for Ag-citrate. The similar case also is found for the coordination between Ag and 3-MPA. The difference in the FTIR spectra is due to the strong coordination between Ag and citrate molecules, namely from the COO- group and also between silver and the S group at 3-MPA. Colorimetric tests have been carried out on Ag-Citrate and AgMPA by utilizing the avidin-biocytin complex which shows that Ag-Citrate and Ag-MPA have the same tendency with Au-citrate and Au-MPA in previous studies. The results of this study can then be used to develop colorimetric assays based on silver nanoparticles to improve the sensitivity and accuracy of measurements of sensor devices with very small amounts of analyte.